The Effect of Working Capital and Sales on Net Profit of Agricultural Sector Companies Listed on the Indonesia Stock Exchange (IDX) in the 2020–2024 Period - Sri Suria Partiwi; Makmur Makmur; Yulfita Aini; Rajiv Khosla (PT. Hidayat Muda Intelektual, 2026)
This study aims to examine the effect of working capital and sales on net profit in agricultural sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative approach using secondary data obtained from the financial statements of agricultural sector companies. The sample consists of seven companies selected through purposive sampling, resulting in 35 firm-year observations. Data were analyzed using multiple linear regression with the assistance of SPSS software.The results show that working capital has a positive and significant effect on net profit, indicating that effective management of current assets and current liabilities contributes to improving company profitability. In contrast, sales do not have a significant effect on net profit, suggesting that increased sales do not necessarily lead to higher profitability due to operational costs and other financial factors. However, the simultaneous test indicates that working capital and sales together significantly influence net profit. The coefficient of determination shows that the independent variables explain a substantial portion of the variation in net profit.These findings highlight the importance of efficient working capital management in supporting the financial performance of agricultural companies. The study provides managerial implications for improving financial management practices and contributes to the literature on corporate financial performance in the agricultural sector.